2017
DOI: 10.1080/24750573.2017.1326742
|View full text |Cite|
|
Sign up to set email alerts
|

The psychiatric assessment schedule for adults with developmental disability checklist: reliability and validity of Turkish version

Abstract: Aim/background: There is a lack of psychometric instruments to measure psychopathology in people with intellectual disabilities (ID). This may lead to underdiagnosis of treatable psychiatric comorbidities in this population. Psychiatric assessment schedule for adults with developmental disabilities (PAS-ADD) Checklist was developed as a screening tool designed for lay people. The PAS-ADD Checklist was created in English and was later on validated for other languages, including French and German. There is no ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Each diagnostic category has a threshold value (6 for affective/neurotic, 5 for organic, 2 for psychotic), indicating the person with intellectual disabilities can be referred to an appropriately qualified professional for a full mental health assessment. The PAS‐ADD Checklist (Revised) was recently validated for Turkish‐speaking populations by a study carried out in Turkey (Görmez & Kırpınar, 2017b), which showed its utility as a general screening tool for psychiatric disorders in clinical practice. PAS‐ADD Checklist (Revised) also includes a section about life events in the past 2 years experienced by the person with intellectual disabilities, such as illness or bereavement.…”
Section: Methodsmentioning
confidence: 99%
“…Each diagnostic category has a threshold value (6 for affective/neurotic, 5 for organic, 2 for psychotic), indicating the person with intellectual disabilities can be referred to an appropriately qualified professional for a full mental health assessment. The PAS‐ADD Checklist (Revised) was recently validated for Turkish‐speaking populations by a study carried out in Turkey (Görmez & Kırpınar, 2017b), which showed its utility as a general screening tool for psychiatric disorders in clinical practice. PAS‐ADD Checklist (Revised) also includes a section about life events in the past 2 years experienced by the person with intellectual disabilities, such as illness or bereavement.…”
Section: Methodsmentioning
confidence: 99%
“…Ölçeğin Türkçe geçerlilik ve güvenilirlik çalışması yapılmıştır ve 0,75 Cronbach alfa değeri ile güçlü bir iç tutarlık gösterilmiştir. Ölçeğin Türkçe sürümünün duyarlılığı %78,7 iken özgüllüğü %78,8 olarak bulunmuştur (15) Az sayıda olduklarından hiç eğitim almayan 4 kişi dışarıda bırakılarak yapılan tek yönlü ANOVA analizinde bakım verenlerin eğitimi ile bakım yükü arasında anlamlı bir ilişki olduğu görüldü (p=0,030). En yüksek bakım yükü puanı (62,91±11,28) üniversite mezunu aile bireylerine aitti.…”
Section: Gelişimsel Bozukluğu Olan Yetişkinlerde Psikiyatrik Tarama öLçeği (Gby-ptö)unclassified